Characterization of the Hazara Virus and Tick cell lines interactions towards Crimean-Congo Haemorrhagic Fever Virus control - Monteiro, Filipe Miguel Tomaz (2022)
Tomaz, F., Antunes, S., Parreira, R., Domingos, A., Seixas, G.,” Characterization of Hazara virus infection in Hyalomma lusitanicum tick cell line.” Poster ID: 185. National Congress of Microbiology and Biotechnology-MicroBiotec2. 23rd – 26th November 2021 (Online Web-conference)